Metodología para el control de costos en Procesos de menor cuantía de obras aplicando La técnica del valor ganado - Palacios Tacuri, Verónica Alexandra (2017)
In the present investigation we analyzed the methodology for the control of costs in processes of smaller quantity of works applying the technique of value gained in construction projects, where we analyzed the main aspects of the indices that influence in the control of costs applying (CVI, EAC, EAC, VAC), and the indicators of cost projections (TCP, ETC, EAC, VAC), and, Thus avoiding cost overruns due to the inadequate control of the changes that occur in the base line of costs of the smallest processes. The main objective of the investigation was to determine a cost control methodology in the process of lower amounts of works by applying the Value of Lives technique to identify the variations between the budget planned and executed through the application of A research of a qualitative type that consisted in the bibliographical - documentary revision of terms related to the research topic; We studied theories of authors of scientific journals that allowed to expand the knowledge on the control of costs through the technique of value gained in civil works. Finally, it culminates with the proposal of a methodology for controlling costs in the process of lower quantity of works applying the technique of earned value, the same that consisted in the development of a flow chart that gives the necessary steps that contractors and others Persons who carry out civil works must continue to control costs in smaller adjudicated processes and determine whether they should carry out preventive or corrective measures based on the interpretation of the indicators of the value-for-money technique, and then make the conclusions and recommendations of the investigation